Research on the Influence of Rumors on Consumers' Irrational Purchasing Behavior under Public Crisis in the Era of Big Data. Issue 3 (April 2021) - He, Jiahui; Mou, Yan; Zhang, Zhengjie
Abstract: Based on COVID-19 and Persuasion Communication Theory, this study constructs a research model to analyze the influence of rumors on consumers' irrational purchasing behavior in the context of public crisis. Using an online questionnaire survey, the empirical results show that information quantity, content features, platform credibility, and source credibility all have a significant positive impact on rumor credibility; rumor credibility has a significant positive impact on negative emotion; Negative emotions have a significant positive impact on irrational purchasing behavior. The platform, source, quantity, and content features of rumors will affect people's trust in rumors. Rumors cause social panic and lead to a surge of negative emotion, making people lose rational judgment and make irrational purchasing behavior. These irrational behaviors are largely due to the panic about some rumors, the urgency, and suddenness of public crisis events, making people more willing to believe in the uncertain information and engage in some irrational consumption behaviors.